ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI SEBELUM DAN MASA PANDEMI COVID-19 - Sirotun Nabawiyah; Jaeni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to determine the analysis of differences in financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic as measured using ratios, solvency ratios, activity ratiod, and profitability ratios. The method used is purposive sampling where from 62 companies there are 47 companies used in the study based on certain considerations in accordance with the criteria carried out. The type data used id secondary data obtained from the Indonesia Stock Exchange in the form of Property and Real Estate annual report for the period 2019-2020. The ratios used in this study are Cash Ratio (CR), Debt to Assets Ratio (DAR), Total Assets Turn Over (TATO), dan Return On Assets (ROA). The result of this study indicate thet the Debt to Assets Ratio (DAR), Total Asset Turn Over (TATO), and Return On Assets (ROA) have significant differences. While the Cash Ratio (CR) there is no significant difference.